2008
DOI: 10.3797/scipharm.0803-10
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of New 2-Substituted-5-{2-[(2-halobenzyl)thio)phenyl}-1,3,4-oxadiazoles as Anticonvulsant Agents

Abstract: A new series of 2-substituted-5-{2-[(2-halobenzyl)thio)phenyl}-1,3,4oxadiazoles was designed, synthesized and investigated for anticonvulsant activities. The designed compounds contain the main essential pharmacophore for binding to the benzodiazepine receptors. Conformational analysis and superimposition of energy minima conformers of designed molecules on estazolam, a known benzodiazepine receptor agonist, revealed that the main characteristics of the proposed benzodiazepine pharmacophore were well matched. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The reaction mixture was stirred at room temperature for 18 hr and was poured into water (30 ml). After extraction with methylene chloride (20 mL × 2), the combined organic layers were dried over MgSO 4 . Filtration and evaporation of the organic solvent gave a crude solid, which was purified with methanol to yield 9 (yield: 35%, m.p: 180-182°C).…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction mixture was stirred at room temperature for 18 hr and was poured into water (30 ml). After extraction with methylene chloride (20 mL × 2), the combined organic layers were dried over MgSO 4 . Filtration and evaporation of the organic solvent gave a crude solid, which was purified with methanol to yield 9 (yield: 35%, m.p: 180-182°C).…”
Section: Synthesismentioning
confidence: 99%
“…[1] Among these, the 1,3,4-oxadiazole skeleton has garnered considerable interest owing to its diverse biological properties including anti-inflammatory, antimicrobial, anticonvulsant, antitubercular, antiviral, and anticancer activities. [2][3][4][5][6][7] 1,3,4-Oxadiazole is called oxybiazole. [8] 4H-chromen-4-one makes up flavone, which is a plantderived secondary metabolite.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the previously reported article revealed that thiazolidinone derivatives exhibit anticonvulsant activity (Tripathi et al, 2014[21]). Based on these evidences and our earlier published papers on flexible novel heterocyclic compounds (Akbarzadeh et al, 2003[1]; Almasirad et al, 2004[4]; Zarghi et al, 2005[24]; Almasirad et al, 2007[5]; Zarghi et al, 2008[22]; Mahdavi et al, 2010[13]; Faizi et al, 2012[7]; Tabatabai et al, 2013[20]; Zarghi et al, 2008[22][23]; Faizi, et al, 2015[6]) , some new thiazolidinone derivatives that have the essential pharmacophore groups for binding to the BZD's receptors were developed (Figure 1(Fig. 1)).…”
Section: Introductionmentioning
confidence: 99%
“…1,3,4-Oxadiazole was found to possess a wide spectrum of pharmacological activity such as antibacterial [3][4] , anti fungal [5][6] , anthelminitic 7 , anti tubercular 8 , anti-infective 9 , anti cancer 10 , anti-HIV 11 , anti oxidant 12 , analgesic [13][14] , anti histanamic 15 , insectivdal 16 , anti-inflammatory 17 , and anti convulsant [18][19] .…”
Section: Introductionmentioning
confidence: 99%